Experimental Study on the Effects of Hydrogen Injection Strategy on the Combustion and Emissions of a Hydrogen/Gasoline Dual Fuel SI Engine under Lean Burn Condition - Shiyi Pan; Jinhua Wang; Bin Liang; Hao Duan; Zuohua Huang (Applied Sciences, 2022)
Hydrogen addition can improve the performance and extend the lean burn limit of gasoline engines. Different hydrogen injection strategies lead to different types of hydrogen mixture distribution (HMD), which affects the engine performance. Therefore, the present study experimentally investigated the effects of hydrogen injection strategy on the combustion and emissions of a hydrogen/gasoline dual-fuel port-injection engine under lean-burn conditions. Four different hydrogen injection strategies were explored: hydrogen direct injection (HDI), forming a stratified hydrogen mixture distribution (SHMD); hydrogen intake port injection, forming a premixed hydrogen mixture distribution (PHMD); split hydrogen direct injection (SHDI), forming a partially premixed hydrogen mixture distribution (PPHMD); and no hydrogen addition (NHMD). The results showed that 20% hydrogen addition could extend the lean burn limit from 1.5 to 2.8. With the increase in the excess air ratio, the optimum HMD changed from PPHMD to SHMD. The maximum brake thermal efficiency was obtained with an excess air ratio of 1.5 with PPHMD. The coefficient of variation (COV) with NHMD was higher than that with hydrogen addition, since the hydrogen enhanced the stability of ignition and combustion. The engine presented the lowest emissions with PHMD. There were almost no carbon monoxide (CO) and nitrogen oxides (NOx) emissions when the excess air ratio was, respectively, more than 1.4 and 2.0.